Pedestrian-Vehicle Conflict Identification Method and Safety Evaluation Model Based on an Improved TAdv: An Example of Signal Intersections in China - Lin Sheng; Guozhu Cheng; Tianyi Li; Haoyu Wang (Journal of Advanced Transportation)
Due to the high incidence of pedestrian collisions at intersections and the vulnerable status of pedestrians, an increasing number of researchers are focusing on pedestrian safety. Currently, researchers tend to apply surrogate safety measures (SSMs) in pedestrian safety analysis, with Time to Collision (TTC) and Post Encroachment Time (PET) being the most widely used. However, their application is subject to certain conditions and limitations. Therefore, this study proposes a novel traffic conflict indicator called improved Time Advantage (improved TAdv), designed to identify pedestrian-vehicle conflicts without collision trajectories. A conflict model for right-turning vehicles and pedestrians at signalized intersections is developed to analyze the impact of various factors on the probability of pedestrian-vehicle conflicts. The results indicate that the improved TAdv offers advantages over traditional traffic conflict indicators. Meanwhile, the findings emphasize the spatial disparities of right-turning pedestrian-vehicle conflicts and analyze the impact of vehicle speed at different locations on the likelihood of such conflicts, offering new insights into pedestrian safety analysis.